Active Learning â€œFactory of Boxesâ€ in the Teaching-Learning Processes in Engineering and Entrepreneurship - Silva, Ricardo; Garcez, Ana; Gomes, Maria; Morais, AntÃ³nio; Lima, TÃ¢nia; Charrua, Fernando; Franco, MÃ¡rio (Journal of Technical Education and Training, 2021)
â€œFactory of Boxesâ€ is an Active Learning (AL) where concepts related to Industrial Engineering, Mechanics, Mechatronics, Electrotechnics and Entrepreneurial Management can be cultivated. The interconnection of these concepts offers the possibility of developing skills in the most diverse areas of knowledge. It is the use of AL, simulating the method of a factory which produces cardboard boxes in different layouts and production systems, namely: (a) Classic Taylorist-Fordist Model; (b) Positionsâ€™ Enrichment Volvo Model; (c) cell production Toyota Model; and (d) automated line Taylorist-Fordist Classic Model. Data collection was based on observation, counting and recording production in a simulated test at two Universities (UFPB â€“ Brazil and UBI â€“ Portugal) involving master students in Industrial Engineering. The data were analysed from the aspects of productivity and cycle-time. The results showed: (a) It is an economically viable AL since it uses low-cost materials (except for simulating with automated posts which requires some investment) and (b) the Classic Model has the highest cycle-time and the Toyota Model has higher productivity, although these results derive from simulations with a teaching-learning aim and cannot be generalized. With the involvement of students-apprentices, knowledge was absorbed through layout-sharing and analysis of work organisation modelsâ€™ dynamics, involving activities using Engineering, Industrial Management and Entrepreneurship tools and concepts.